Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Kelokopi Batusangkar - Andrika Aldi; Violintikha Harmawan (Tamasya : Jurnal Pariwisata Indonesia, 2025)
The purpose of this study was to find out how service quality affects customer happiness at Kelokopi Batusangkar, which was shown by comments about unsteady Wi-Fi connections, uneven drink tastes, and slow service from staff who didn't know the menu. What the study aims to do is show how service quality affects customer happiness. A non-probability picking method was used to select 370 people for the study, which used a detailed quantitative approach and a cause correlation method. A Likert-scale questionnaire that had been checked for validity and reliability was used to collect data, and SPSS 24.00 was used to analyze the results.The findings showed that 83% of people were satisfied with the service quality and 78% were satisfied with the service quality. Only 31.2% of customer happiness was caused by service quality; the other 69.8% was caused by other things.